ANALISIS PERBEDAAN KASUS RUJUKAN OBSTETRI SELAMA PANDEMI COVID 19 - eny susanti (NHM PRESS, 2021)
Health problems in Indonesia that still need to be watched out for are those that occur in the group of mothers and children, which can be seen from the still high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). In this condition, the quality of midwifery referral services cannot be separated from the referral system implemented by village midwives as the front service post in the community, especially during the current COVID-19 pandemic. During the COVID-19 pandemic, it was found that the patient refused to be referred by the midwife because the health protocol at the referral facility required an antigen test at the hospital. This causes a decrease in the number of maternal referrals from FKTP. The purpose of this study was to determine the number of referral cases before and during the Covid-19 pandemic at PMB Silvi, Kowel Health Center Work Area. The method in this study uses descriptive research. The population in this study were all referral cases in September 2019-September 2020 as many as 44 cases. The sample in this study were all referral cases at PMB Silvi. Data collection uses secondary data, namely the midwife reference book. Based on the results of research at PMB Silvi, the Kowel Health Center working area, it was found that before the covid-19 pandemic there were 30 referral cases of pregnant women who were willing to be referred, while during the pandemic there were 14 referrals of pregnant women who refused to be referred, referral cases decreased because pregnant women were unwilling following the covid-19 procedures at advanced health facilities. Independent Practice Midwives are expected to be able to provide education regarding the Covid-19 health protocol in first and advanced level health services and it is hoped that midwives will never get bored to always provide KIE or counseling to the public regarding health protocols and referral procedures during the pandemic to help reduce the level of MMR and IMR.